Antifungal drug price increases in the United States, 2000–2019. Issue 9 (18th July 2022) - Thomas, Christine M.; Shae, Whitney; Koestler, Devin; DeFor, Terese; Bahr, Nathan C.; Alpern, Jonathan D.
Abstract: Background: Antifungal drugs treat a variety of conditions, ranging from localised dermatologic disease to life‐threatening systemic infections. Some common antifungal drugs experienced large price increases in recent years, however, factors contributing to these price increases are poorly understood. We sought to examine trends in antifungal drug prices and determine underlying drivers of price changes. Methods: Antifungal drug products in the United States were identified using the Food and Drug Administration (FDA) Label database. For each product, we determined the wholesale acquisition cost per unit over time between 2000 and 2019, adjusting for inflation, and examined variables that could impact price: route of administration, number of FDA indications, the quantity of professional guideline recommendations, use for prophylaxis, number of FDA‐approved manufacturers, and whether it was compounded. Price trajectories were clustered into four groups: (1) stable, 2) moderate, (3) high, and (4) extreme price increases. Results: Of 139 identified drug products, one outlier was removed due to exorbitant price increases. Cluster 1 ( n  = 31) demonstrated the most stable prices with a 25% mean price increase. Clusters 2 ( n  = 97), 3 ( n  = 7), and 4 ( n  = 3) demonstrated moderate, high, and extreme price increases with 52%, 318%, and 900% mean price increases, respectively. Atypical routes of administration and compounding were over‐represented in clusters 3 and 4. There was no correlation between the number of manufacturers and price changes. Conclusions: Antifungal drugs exhibited large, inflation‐adjusted price increases. Atypical routes of administration and compounding were over‐represented within clusters exhibiting extraordinary price increases. Our data support policies aiming to curb large price increases for medically important drugs.